Ray-tracing based atmospheric propagation simulator for a 2x2 LOS MIMO system - Zhou, Yongan (My University, 2023)
A microwave radio system with multiple antennas is one popular technology for backhaul network deployment to reach the capability increase required for 5G and 6G. Antenna separations at transmit and receive sites should be carefully designed to ensure a proper phase relation, in this Multiple Input Multiple Output (MIMO) system with long Line-of-Sight (LoS) paths between transmitter and receiver. The LOS MIMO system may fail to operate under an extremely refractive atmosphere due to a lack of sufficient system gain which is determined by the power level and phase condition of the received sub-streams. The contribution of the thesis is to provide a simulator that can model radio’s at mospheric propagation, and it can be further used to verify real link measurement data. It is tested that the simulator has minor accuracy loss over the propagating distance concerned in this study. The simulation of electromagnetic wave propa gation is based on Forward Ray Tracing (FRT). The results demonstrate that the simulator is capable of predicting channel performance (MIMO gain, MIMO phase, etc.) for a 2-by-2 LOS MIMO system over a refractive atmosphere. The results also demonstrate that the simulator is found to be in good agreement with the lit erature and with Parabolic Equation (PE) methods, validating its potential use for predicting the outage probability for the MIMO link. This study, to the author’s best knowledge, is the first work that models the im pact of atmospheric refractivity on LOS MIMO channels using FRT. It is found that for a 2x2 LOS MIMO system the antenna separation calculated assuming free space propagation is also valid for the case of standard refractivity. For other re fraction conditions, the link will more likely experience an outage due to variation in phase condition than loss of power. In addition, atmospheric multipath may in duce random MIMO phase variation. However, the simulator cannot yet properly tackle surface-induced effects on the signals; this requires further development of the software.
Keywords: Line-of-Sight, radio propagation, troposphere duct, wireless backhaul, atmospheric refraction, microwave link planning